'We achieve the impossible': Discourses of freedom and escape at music festivals and free parties. (November 2018) - Griffin, Christine; Bengry-Howell, Andrew; Riley, Sarah; Morey, Yvette; Szmigin, Isabelle
In this article, we explore the notion of freedom as a form of governance within contemporary consumer culture in a sphere where 'freedom' appears as a key component: outdoor music-based leisure events, notably music festivals and free parties. 'Freedom' is commodified as central to the marketing of many music festivals, which now form a highly commercialised sector of the UK leisure industry, subject to various regulatory restrictions. Free parties, in contrast, are unlicensed, mostly illegal and far less commercialised leisure spaces. We present data from two related studies to investigate how participants at three major British outdoor music festivals and a small rural free party scene draw on discourses of freedom, escape and regulation. We argue that major music festivals operate as temporary bounded spheres of 'licensed transgression', in which an apparent lack of regulation operates as a form of governance. In contrast, free parties appear to 'achieve the impossible' by creating alternative (and illegal) spaces in which both freedom and regulation are constituted in different ways compared to music festival settings.